Review of the Use of Indrive Online Transportation Services from the Aspects of Service Quality, Price, and Promotion on Purchasing Decisions in Manado City - Sumolang, Gracia; Mongkareng, Injili; Asaloei, Sandra Ingried (Asia Pacific Journal of Interdisciplinary Studies, 2025)
This research aims to analyze the user perspective on the use of Indrive online transportation, focusing on service quality, pricing, and promotions in relation to purchase decisions. The research employs a quantitative approach, utilizing a questionnaire as the data collection tool. The study population consists of residents of Manado City who use the Indrive application. The sample size includes 30 respondents, comprising 6 male and 24 female participants. The research findings indicate that the utilization of Indrive online transportation services in Manado City significantly influences respondents' purchase decisions, particularly in terms of service quality, pricing, and promotional activities.